2007
DOI: 10.1007/s11701-007-0035-9
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted laparoscopic radical cystectomy: initial experience on 27 consecutive patients

Abstract: Recent reports have demonstrated that robot-assisted laparoscopic cystectomy is technically feasible. We report technical and functional results of a large series of patients undergoing laparoscopic cystectomy with the da Vinci surgical system (DVSS). A total of 27 patients (24 males) underwent laparoscopic radical cystectomy with the DVSS (intuitive surgical) between January 2004 and December 2005. Indications for cystectomy were muscle-invasive transitional cell carcinoma (TCC) or leiomyosarcoma of the urina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In some early, small series, Mottrie et al [9] and Murphy et al [12] reported sufficient erections in six of seven and three of four men, respectively. Similar to well-described literature on RARP, Table 8 summarizes comparative studies evaluating lymph node yield after ORC, LRC, and RARC.…”
Section: Potency Recovery After Robot-assisted Radical Cystectomymentioning
confidence: 95%
See 1 more Smart Citation
“…In some early, small series, Mottrie et al [9] and Murphy et al [12] reported sufficient erections in six of seven and three of four men, respectively. Similar to well-described literature on RARP, Table 8 summarizes comparative studies evaluating lymph node yield after ORC, LRC, and RARC.…”
Section: Potency Recovery After Robot-assisted Radical Cystectomymentioning
confidence: 95%
“…Only three of six series reported using a distinct definition for continence, which was generally no pad or one pad (safety) per day. One of the earliest RARC series reported an 86% continent rate (seven of eight men) after 3.5 mo [9]. More recent series published 6-mo continence rates of 48-100% for daytime continence and 11-100% for nighttime continence.…”
Section: Functional Informationmentioning
confidence: 97%
“…Continence figures are relevant to those patients undergoing orthotopic neobladder at the same time as male NS RARC and satisfactory continence is defined in the studies to be dry enough to maintain with a maximum of one pad per day. In this review, 85.06% day time continence rate (range 54.5%-100%) and 72.48% night time continence rate (range 46.7%-88%) were noted overall in patients whose NVBs were preserved [13,17,18,[20][21][22]26,[29][30][31][33][34][35][36][37][38][39][40] . This is in contrast to the results of some studies, for example, Tyritzis et al [38] , who noted no significant difference in continence rates between their NS and non-NS groups of patients with 88.2% and 88.9% respectively for day time continence rates at 12 months.…”
Section: Discussionmentioning
confidence: 96%
“…Beyond the field of ophthalmology, the da Vinci system has been used by neurosurgeons to investigate the feasibility of minimally invasive skull base surgery using a supraorbital trans-eyebrow keyhole approach 16. Robot-assisted muscle surgery has also been reported for many large muscles, such as latissimus dorsi, diaphragm, Heller, bladder, vagina, and pelvic muscles 1719…”
Section: Discussionmentioning
confidence: 99%